Anti-Convulsant Drugs Prescribing Pattern and Efficacy Comparison in Paediatric Epilepsy Population in a Tertiary Care Teaching Hospital - Antham, Mounika; Mulukuntla, Mounika; Puchchakayala, Goverdhan; Guduru, Vijay Kumar (Indian Journal of Pharmacy Practice)
Objectives: To conduct the study of the drug usage pattern and its efficacy and tolerability comparison of most commonly used anti-epileptic drugs. Methods: The data included patient’s age, sex, types of seizure, aetiology, past and present treatments, dose and duration of therapy and associated adverse effects. A total of 150 subjects (children) who received Sodium valproate (n=88), Carbamazepine (n=21), Phenytoin (n=7), Clobazam (n=11), Levetiracetam (n=4) and remaining in combinations (n=19) as long-term management, were enrolled in the study. Assessed for a period of 12 months for the management of seizures and also the adverse effects incidents. Results: Total, 91 (60.7) subjects endured from seizure episodes throughout the study interval of 12months. 131 (87.3%) patients were treated with Monotherapy, the rate of seizure remission was 81 (61.8%) and 19 (12.6%) patients were with multidrug therapy, the rate of seizure remission was 11 (57.8%). The rate of seizure remission was found statistically significant.60 patients treated with Sodium Valproate, 19 patients treated with Carbamazepine, 1 patient treated with Phenytoin, 9 patients with Clobazam, 2 patients treated with Levetiracetam were observed to be seizure free. The most commonly occurred type of seizures was GTCS and Focal/Partial type. Overall, 67 (44.6%) patients had adverse effects; of the highest incidence was cognitive impairment, mood alterations and dizziness which developed more often with Sodium Valproate and Carbamazepine. Conclusion: In our collected and observed study in tertiary care teaching hospital the majority of patients were prescribed with Sodium Valproate and Carbamazepine. It appears that Sodium Valproate and Carbamazepine has highest efficacy rate and Levetiracetam had better tolerability. Sodium valproate and Carbamazepine had balanced effectiveness and tolerability.
Keywords: Anti-epileptic drugs; Efficacy; Tolerability; Monotherapy; Polytherapy; reoccurrence.